2010
DOI: 10.1109/tuffc.2010.1420
|View full text |Cite
|
Sign up to set email alerts
|

Power deduction from surface fields in multilayer waveguides

Abstract: This paper proposes a method to estimate power carried by a propagating Lamb mode in an arbitrary multilayer waveguide from calculated or measured surface displacements. To this end, we calculate the so-called mode power coefficient relating the surface amplitude of the mode to the total power flow toward the lateral direction. The coefficient is given by the gradient of the effective acoustic admittance with respect to the lateral wavenumber, and can be readily calculated by slightly modifying software codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the figure, the relative power of each reflected mode is shown, as well as the power reflection coefficient R p . Here 1 − R p is approximately the amount of transmitted power to the second waveguide; exemplar analysis of forward-scattered power as presented in [15] showed that the error in energy conversation is small for all points. In general, for h′/h < 0.1, back-scattering as the respective incident mode becomes dominant, coinciding with the result in Fig.…”
Section: B Peripheral Connected Fbar Edgementioning
confidence: 99%
See 1 more Smart Citation
“…In the figure, the relative power of each reflected mode is shown, as well as the power reflection coefficient R p . Here 1 − R p is approximately the amount of transmitted power to the second waveguide; exemplar analysis of forward-scattered power as presented in [15] showed that the error in energy conversation is small for all points. In general, for h′/h < 0.1, back-scattering as the respective incident mode becomes dominant, coinciding with the result in Fig.…”
Section: B Peripheral Connected Fbar Edgementioning
confidence: 99%
“…For the calculation of the carrying power P of single waveguide modes, we used the method presented in [15], in which, after obtaining the relative mode surface amplitude in the waveguide far field by a 1-d-FFT, the respective mode powers can be deduced by relating them to mode power coefficients. With the respective powers of the forward-and backward-traveling modes determined, one is able to compare the mode power of the incident mode P inc with that of the back scattered modes P ref,i in the waveguide.…”
Section: B Practical Setupmentioning
confidence: 99%
“…Left border Right border Both the active region and the passive region can be regarded as acoustic waveguides, where lateral power transport occurs in terms of the eigen modes. To determine these theoretic power transport mechanisms, the dispersion behavior for the frequency region of interest was calculated by using the effective acoustic admittance 7) and is shown in Fig. 2.…”
Section: Si Substratementioning
confidence: 99%
“…By using the acoustic admittance, we also obtain mode power coefficients 7) c n for the four propagating modes in the active area and PL in the passive area (Table I). They allow concluding from the square of the surface amplitude A 2 n to the mode power P n over…”
Section: Investigated Areamentioning
confidence: 99%
See 1 more Smart Citation